Cyclical Multiplier and Zero Low Bound Effects of Government Expenditure on Economic Growth: Evidence for Greece. (June 2017) - Alexiou, Constantinos; Nellis, Joseph G.
Abstract : This study explores the impact of government expenditure multipliers on economic growth utilising an Autoregressive Distributed Lag (ARDL) approach. We provide evidence on the short‐term dynamics as well as the long‐run expenditure multiplier effects on economic growth for the Greek economy over the period 1960–2014. We find that the size of the multiplier does not differ substantially over the phases of the business cycle. Our results also indicate that irrespective of the scale of inflation, government expenditure positively affects economic growth, whilst inconclusive evidence is obtained in the case of exceptionally low interest rates.